Pharmacokinetics of Hydrogen During Hydrogen-Saturated Saline Infusion in Pigs - Masaki Shibuya; Masafumi Fujinaka; Mako Yonezawa; Natsumi Nishimura; Hitoshi Uchinoumi; Hiroshi Sunahara; Kenji Tani; Eiji Kobayashi; Motoaki Sano (Biomedicines)
Background: Hydrogen gas (H2) has been shown to be effective in the treatment of various clinical conditions, from acute illnesses to chronic illnesses. However, its clinical indications and the corresponding appropriate hydrogen delivery methods have yet to be determined. This is due to the fact that the pharmacokinetics and pharmacodynamics of hydrogen in each delivery method have not been experimentally proven. Here, we verified the pharmacokinetics of hydrogen after the infusion of hydrogen-saturated saline. Methods: Hydrogen-saturated saline was prepared and checked for sterility and component specifications. Hydrogen-saturated saline was administered intravenously (125 mL/h) through the left internal jugular vein of pigs, and the blood hydrogen concentration was measured over time. Results: It was confirmed that hydrogen can be safely mixed under pressure into intravenous solutions (pharmaceutical products) without the contamination of foreign substances by using a needle-less vial access cannula. No change in the PH or composition of the solution was observed due to hydrogen filling. The hydrogen concentrations of blood samples collected from the left internal jugular vein 3 cm to the heart from the tip of the infusion line were 6.4 (30 min), 4.7 (60 min), 4.9 (90 min), and 5.3 (120 min) ppb w/w, respectively. The hydrogen concentrations of blood samples collected from the right atrium were 0.7 (30 min), 0.5 (60 min), 0.7 (90 min), and 0.7 (120 min) ppb, respectively. The hydrogen concentration of blood samples collected from the right internal carotid artery were 0.1 (pre), 0.2 (30 min), 0.3 (60 min), 0.0 (90 min), and 0.0 (120 min) ppb w/w, respectively. Conclusions: We confirmed that hydrogen could be safely pressurized and filled into intravenous (pharmaceutical) solution without contamination by foreign objects using a needle-free vial access cannula. When saturated hydrogen saline was dripped intravenously, almost all of the hydrogen was expelled during its passage through the lungs and could not be supplied to the arterial side.